Performance of layer-by-layer (LbL) polyelectrolyte forward osmosis membrane for humic acid removal and reverse solute diffusion (Chemical Engineering Research Bulletin, 2017)
Recent study claimed that forward osmosis (FO) process could handle the fouling problem due it driven force based on natural osmotic pressure. However, researchers observed that FO membrane had problem with reverse solute diffusion (RSD) of draw solution. Therefore, FO membrane properties must be improved either physically or chemically in order to overcome this problem. Among all, surface modification approach has been acknowledged as a best technique to alter the membrane properties without significantly change the bulk membrane properties. In this study, polyelectrolyte FO membrane has been produced through Layer by Layer (LbL) deposition method by using Poly (diallyl-dimethylammoniumchloride), PDADMAC and Poly (sodium 4-styrene-sulfonate), PSS as an active monomers. Humic acid (HA) as part of Natural Organic Matter constituents was used as the feed solution and NaCl as a draw solution. The chemical structure and morphology of the FO membrane were characterized by FTIR and FESEM, respectively. From this study, the highest water flux and humic acid rejection were achieved at 2.5M of draw solution with value of 2.56 L/m².h and 99%, respectively. In general, the water flux increases as the concentration of draw solutions were increased. However, it was observed that reverse salt diffusion (RSD) become worse at higher concentration of draw solution.Chemical Engineering Research Bulletin 19(2017) 75-79